Az utolsó császár Magyarországon – Hailé Szelasszié 1964-es látogatása - Marsai, Viktor (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
The visit of the Ethiopian emperor Haile Selassie on 20-23 September 1964 was one of the most important events of the Hungarian foreign relations that time. This article aims to examine the circumstances of the meeting and its effects on the Ethio-Hungarian relations. The main statement of the paper is that although the visit did not bring a breakthrough in the collaboration, it helped to strengthen and fill with content the fresh connection between the parties, and it also determined the main frameworks of cooperation for the next two and half decades. Furthermore, the negotiations bred important practical experiences for the Hungarian administration, which knowledge helped not only in the relations with the developing world, but also in the wider international arena.